Pengaruh conditional value, emotional value, epistemic value dan green self identity terhadap green purchase intention konsumen Generasi Z Kota Palembang - Lilis Permata Sari; Budi Setiawan; Endah Dewi Purnamasari (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2025)
The United Nations (UN) has set 17 goals to protect the earth, considering that natural assets are increasingly depleted along with the increase in the world's population. Responding to the UN's call regarding this global issue, Reliable Consumption and Production can influence consumers' desire to consume. This indicates that the factors of Conditional value, emotional value, curiosity value, and Green Personality on Green purchase Considerations of Generation Z consumers in Palembang City. The research strategy used in this study is a descriptive Quantitative Strategy using the SmartPLS version 3 program, the population of this study is generation Z aged 17-27 years with data collection using an online survey. The sample tested was 105 respondents. The results of this study illustrate that the factors of Conditional value, Epistemic Value, green self-identity have a significant influence on Green purchase Intention but emotional value does not have a major impact on the Green purchase Intention of Generation Z consumers in Palembang City. Based on the results of the considerations, it was found that increasing consumer awareness of products in the environment as a whole affects green buying interest.